Variability effects on magnetohydrodynamic for Blasius and Sakiadis flows in the presence of Dufour and Soret about a flat plate - Anselm O. Oyem; Winifred N. Mutuku; Abayomi S. Oke (Engineering Reports, 2020)
Abstract A study on a steady‐state, two‐dimensional boundary layer flow of an incompressible magnetohydrodynamic fluid for the Blasius and Sakiadis flows about a flat plate in the presence of Dufour (Df) and Soret Sr has been carried out. The governing partial differential equations are transformed into a set of coupled nonlinear ordinary differential equations using similarity variables. These coupled equations are solved numerically using Runge‐Kutta Gill method with shooting technique. The results obtained have significant effects in the controlling parameters of the flow fluid.